DISKRESI KEPOLISIAN PADA PENGAWALAN KONVOI KOMUNITAS DALAM MASA PANDEMI DI WILAYAH HUKUM POLDA METRO JAYA - Muhammad Ricky; Surya Nita; Yopik Gani (SOSIOEDUKASI, 2022)
The Covid-19 pandemic has affected the way of policing due to social restrictions, but then gathering and expressing opinions in public cannot be prevented, because this is a part of human right. Crowd control during the pandemic, one of which was escorting community convoys, then became a challenging task for the police. This paper aims to analyze the application of police discretion in escorting community convoys during the Covid-19 pandemic. Qualitative methods were used in the development of this research, by conducting literature studies and interviews in collecting data. The analysis in this study is based on discretionary theory and procedural justice theory. The results of the analysis show that currently policing is shifting to adjust to pandemic conditions, one of the important elements is the expansion of the police's discretionary authority in handling pandemics in the field related to law enforcement, especially regarding social restriction policies. This discretion then needs to be applied in public order management and crowd control. The way that the police can do in crowd control is to develop intense communication with the community to create dialogue-based solutions that the community will voluntarily comply with. The implementation of escorting community convoys in the jurisdiction of Polda Metro Jaya shows that the police who carry out escorts are still unable to apply discretion properly, causing discriminatory discretion and non-function discretionary deviations. This then causes public doubts about the ability of the police to exercise discretion in order to achieve justice